Improving the Detrimental Aspects of Salinity in Salinized Soils of Arid and Semi-arid Areas for Effects of Vermicompost Leachate on Salt Stress in Seedlings - Cicek, Nuray; Erdogan, Muhterem; Yucedag, Cengiz; Cetin, Mehmet (Springer Science and Business Media LLC, 2022)
The present study was performed to determine the effects of vermicompost leachate on growth, quality, and nutrients of Sedum album seedlings under salt stress. The study was carried out in Research and Practice Greenhouse of Cankiri Karatekin University in Central Anatolia of Turkey. One-month-old seedlings are treated with or without vermicompost leachate at five various NaCl applications (0, 50, 100, 150, and 200 mM). Shoot height, shoot fresh and dry weights, aesthetic appearance score, and crown widths of 10-week-old S. album seedlings and plant nutrients were evaluated. Salt stress x vermicompost leachate interaction had a significant effect on all studied traits (P < 0.05). The study revealed that vermicompost leachate-supplemented salt concentrations improved the harmful effects of salinity stress on growth and quality traits and macro- and micronutrients of S. album. The present study highlights the consideration of the regular application of vermicompost leachate, rich in nutrient content and microbial activity, to improve the detrimental aspects of salinity in salinized soils of arid and semi-arid areas and to improve the quality of soil and plant.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water